Faktor-Faktor Ketepatan Mengkonsumsi Tablet Tambah Darah Pada Remaja Putri - Setiawati, Ririn; Sholihah, Andri Nur (Jurnal Kesehatan, 2024)
One of the health problems throughout the world, especially in developing countries, where an estimated 30% of its population experiences it, is anaemia. Anaemia is common in society, especially in teenagers and pregnant women. The number of cases of adolescent anaemia is still quite high, and in 2019, the global prevalence of anemia was 29.9% (95% uncertainty interval (UI) 27.0%, 32.8%) in fertile women, equivalent to more than half a billion women aged 15-49 years (WHO, 2019). This study aims to determine the factors (level of knowledge, distribution of Fe Tablets, and teacher support at school) that influence the success of giving Fe Tablets to teenagers at Ma'arif Middle School, Gamping. The type of research used by researchers employed analytical descriptive research, which used a total sampling approach with the chi-square test. This research was conducted in August 2023 with a sample size of 55 female students, and data collection was carried out by filling out a questionnaire. The results of the knowledge of adolescent girls regarding anaemia and Fe tablets were mostly (50.5%) in the good category; school support for consuming Fe tablets in the majority of samples (67.3%) was in the less supportive category, as well as, for accuracy of teenage female students. Most of the students (52.7%) took Fe tablets correctly. The conclusion of this research is that from the three factors studied (knowledge, Fe tablets distribution, and school support), it is known that there is no influence of these factors on the accuracy of consuming Fe tablets at Ma'arif Middle School, Gamping. Keywords: Knowledge, School Support, Fe Tablets.